The Jurisprudential-Legal Review of Ownership of Mines with a Look at Australian and American Law - Mahdi Adami; Jalal Soltan Ahmadi (آموزه‌‌های فقه مدني, 2024)
The failure of rectification of theoretical foundations has led to a plurality of conflicting laws in the field of mining. Civil Code of the Islamic Republic of Iran under the influence of Jaʿfarī jurisprudence on mine ownership considers these resources to be private ownership, while in 1998 in order to preserve the sovereignty of the state over mineral deposits, the new mining law was ratified and established state ownership of mines. In contrast, the two legal systems of Australia and the United States are the leading systems with a coherent basis in the field of mining. It is tried in this article to investigate the methods of mining ownership in the Islamic Republic of Iran, Australia and the United States and it is also tried to investigate the rules of Australian and American mining law on ownership of minerals by individuals after the issuance of multiple licenses and views on ownership of mines in Jaʿfarī jurisprudence. The results of the research show that an interpretation should be presented about the ownership of mines that does not interfere with private property to allow for proper exploitation of mineral deposits and amending the laws.